2021
DOI: 10.1002/adfm.202007457
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Self‐Healing Natural Biopolymer‐Based Hydrogel Adhesive with Thermoresponsive Reversible Adhesion for Minimally Invasive Surgery

Abstract: Biocompatible hydrogel adhesives with multifunctional properties, including injectability, fast self-healing, and suitable on-demand detachment, are highly desired for minimally invasive procedures, but such materials are still lacking. Herein, an injectable self-healing biocompatible hydrogel adhesive with thermoresponsive reversible adhesion based on two extracellular matrix-derived biopolymers, gelatin and chondroitin sulfate, is developed to be used as a surgical adhesive for sealing or reconnecting ruptur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
212
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(213 citation statements)
references
References 38 publications
1
212
0
Order By: Relevance
“…In addition to self-healing and injectability, BOCPG-3 hydrogels also exhibit excellent adhesive properties. The aldehyde groups in the hydrogel react with amino groups on the tissue surface, as previously reported [ 39 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 66%
“…In addition to self-healing and injectability, BOCPG-3 hydrogels also exhibit excellent adhesive properties. The aldehyde groups in the hydrogel react with amino groups on the tissue surface, as previously reported [ 39 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Adhesive materials for use within or on the human body come with a unique set of requirements and challenges: (i) ability to join wet surfaces; (ii) clean removal without damage to tissue; (iii) biocompatibility of constituents; and (iv) mechanical robustness. 3,[20][21][22]160 One strategy to overcome all of these obstacles is to create a polymeric network with cross-linkers that can be broken down by biocompatible chemical stimuli, such as enzymes. [20][21][22][23] Mooney and coworkers reported a class of temporary adhesive materials with strategically selected polymeric hydrogels and cross-linkers that created a sturdy polymeric network with approximately 90% water.…”
Section: Biocompatible Degradation Via Enzymesmentioning
confidence: 99%
“…19 For example, this type of adhesive is extremely promising for biomedical applications, where fragile surfaces, such as organs or healing wounds, must be protected during removal. [20][21][22][23] In contrast, stimuli-responsive materials that demonstrate permanent adhesion aer a stimulating event are especially useful in dentistry, 6,7 wound dressings, 5,23,24 and aerospace engineering. 25,26 Unique characteristics of stimuli-responsive temporary adhesives A stimuli-responsive adhesive is a material designed to promote the joining of two surfaces that exhibits a change in its mechanical and/or adhesive properties aer being exposed to an external stimulus or stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has further shown that HA is very versatile in its use in medical treatment and tissue engineering because of its high biocompatibility, biodegradability, viscoelasticity, and non-toxic characteristics [ 5 , 6 ]. These properties make HA an ideal biomaterial for injectable hydrogels, wound patches, 3D bioprinting, tissue scaffolds, and drug delivery [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the functionalized molecule has no chemical moieties with adhesive properties. These methods do not have the adhesive property needed for certain medical applications such as implant materials for surgical recovery [ 11 , 19 ]. Adhesive properties enable the research to be conducted in the past few years to develop an adhesive HA-derived hydrogel for medical treatment [ 20 ].…”
Section: Introductionmentioning
confidence: 99%